Imaging the ICU Patient - Screaton, Nicholas J.; Falter, Florian (Springer London, 2014)
Work in intensive care is dynamic and often requires swift decision-making to achieve the best patient outcome. This book serves as a practical guide for professionals working in this demanding area of medicine. It reviews diagnostic options as well as strengths and weaknesses of imaging techniques in clinical scenarios familiar to most ICU clinicians. The concise format allows rapid access to key information.   Imaging the ICU Patient is a true collaboration between critical care and radiology. It demystifies the process of deciding when and how to image the critically ill patient. Using a symptom-orientated approach, it addresses techniques as well as patient safety issues. It is meant to be used by critical care clinicians and radiologists and aims to foster a better appreciation of the concerns both specialties have when imaging critically ill patients.